(untitled) (Proceedings OPTIMAL, 2025)
Avocado (Persea Americana Mill.) is one of the plants that can increase hair growth. Secondary metabolite compounds contained in avocado leaves are flavonoids, alkaloids, saponins, tannins, terpenoids which act as antioxidants that can protect hair from chemical care products, pollution, and damaged hair due to lack of nutrition. This study aims to determine the secondary metabolite compounds contained in avocado leaves (Persea Americana Mill.), to determine the difference in hair growth in hair tonic preparations of avocado leaf ethanol extract (Persea Americana Mill.) at concentrations of 2%, 4%, 6%, 8% for male rabbits and to determine the effectiveness of hair tonic avocado leaf ethanol extract (Persea Americana) on hair growth in male rabbits (Oryctolagus cuniculus). This study is included in experimental research using the Completely Randomized Design (CRD) method. The results showed that there are secondary metabolite compounds contained in avocado leaves, namely flavonoids, saponins and tannins. Statistical analysis showed differences in hair growth in male rabbits (Oryctolagus cuniculus) at each concentration of the ethanolic avocado leaf extract hair tonic, namely 6,60 mm (2%), 5,90 mm (4%), 5,31 mm (6%), and 5,25 mm (8%). The results indicate that the most effective concentration of the ethanolic avocado leaf extract hair tonic for promoting hair growth is 2%. Keywords: Avocado leaves, secondary metabolites, hair growth